Nanocolumnar zinc oxide as a transparent conductive oxide film for a blue InGaN-based light emitting diode. Issue 1 (January 2015) - Ameera, Nur; Shuhaimi, Ahmad; Surani, Najwa; Rusop, Mohamad; Hakim, Muhammad; Mamat, Mohamad Hafiz; Mansor, Mazwan; Sobri, Mohd; Ganesh, V.; Yusuf, Yusnizam
Abstract: A comprehensive study of ZnO nanocolumnar structure has been conducted through x-ray diffraction spectroscopy, atomic force microscopy, field emission scanning electron microscopy and UV-visible spectroscopy measurements. This study involves the development of an efficient ZnO transparent conductive oxide film fabricated by RF magnetron sputtering for use in a blue indium gallium nitride based light emitting diode. FESEM measurements revealed that a maximum growth temperature of 500 °C induced the formation of a nanocolumnar structure. The XRD measurements revealed that the stress reduction in the film also contributed to a superior ZnO nanocolumnar structure. In addition, the reduction of the oxygen percentage during deposition resulted in significant improvement of the structure. The reduced atomic peening effect yielded lower stress in the film. Thus, a dense, uniform-thickness, fine nanocolumnar ZnO of lateral size measuring 30 to 60 nm was successfully fabricated at the lowest oxygen percentage of 7%. This film also exhibited good transparency at the blue region with 78% optical transmission.